Integrated Production Control Systems / Management, Analysis, Design 2/(SFs - Bailey Lames E.; Bedworth David D. (John Wiley & Sons, Ltd, 1987)
The Role of Production Control, Production Control Information Flow, Forecasting, Aggregate Planning and Master Scheduling, Materials Requirement Planning, Inventory Analysis and Control, Sequencing and Scheduling, Project Planning, Scheduling with Resource Constraints, Personnel Scheduling, Areas Under the Normal Curve, Documentation for Computer Programs, Index.
The Role of Production Control, Production Control Information Flow, Forecasting, Aggregate Planning and Master Scheduling, Materials Requirement Planning, Inventory Analysis and Control, Sequencing and Scheduling, Project Planning, Scheduling with Resource Constraints, Personnel Scheduling, Areas Under the Normal Curve, Documentation for Computer Programs, Index.